Acute and Subacute Toxicity Assessment of Oxyclozanide in Wistar Rats - Wang, Weiwei; Dong, Zhen; Zhang, Jili; Zhou, Xuzheng; Wei, Xiaojuan; Cheng, Fusheng; Li, Bing; Zhang, Jiyu (Frontiers in Veterinary Science, 2019)
Oxyclozanide is an effective anthelmintic and has shown good properties in other ways including anti-adenovirus, anti-biofilm, antifungal, and antibacterial activity. This study aimed to investigate the acute and subacute 28-days repeated dose oral toxicity of an oxyclozanide suspension in Wistar rats. A high oral lethal dose (LD50) of 3,707 mg/kg was observed in the acute toxicity test. During the 28-days time period, no obvious adverse effects or death were detected. Histopathological changes were observed in the heart, liver, and kidney of animals treated with high dose of oxyclozanide. Based on the hematological parameters, there were no statistical differences between the oxyclozanide-treated group and the control group. For biochemistry assays, ALP, AST, GLU, TBIL, GLO, TG, BUN, UA, LDH, and CK were statistically changed in the treatment groups. These data suggested that the LD50 of oxyclozanide was 3,707 mg/kg body weight (BW), and the lowest observed adverse effect level (LOAEL) of oxyclozanide was at a dose of 74 mg/kg in rats.